Cytotoxic Activity and Phytochemical Analysis of Breynia cernua from Papua - Dirgantara, Septriyanto; Tanjung, Rosye H.R.; Maury, Hendra K.; Meiyanto, Edy (Indonesian Journal of Pharmaceutical Science and Technology, 2018)
Breynia cernua (local name Katuk Hutan) is an Indonesian medicinal plant (family: Euphorbiace- ae) originated from Papua which have been used traditionally as alternative treatment for breast and cervical cancer. The objectives of this research were to investigate potential cytotoxic activity and phytochemical aspect test of B. cernua extract and its fractions. Extraction was performed by macera- tion using ethanol 96%, followed by successive fractionations. Phytochemical screening and in vitro cytotoxic activity test were obtained for extract and active fraction with Brine Shrimp Lethality Test (BSLT) method and MCF-7 tumor cell lines were assessed by 3-(4-5-dimethylthiazol-2yl)-2,5-diphe- nyl tetrazolium bromide (MTT) assay. The results from cytotoxic activity test of breast cancer MCF-7 cell line from ethanolic 96% extract and three fractions: n-hexane, ethylacetate and water fractions showed 246.841 ppm, 165.65 ppm, 562.57 ppm dan 713.78 ppm respectively meanwhile the IC50 value of doxorubicin as the positive control was 6 Î¼M. TLC and phytochemical screening showed the pres- ence of alkaloids, terpenoid, avonoids and tannins compounds in this active plant. Keywords: Antitumor, Breynia cernua, BSLT, MCF-7